Ethnic Differences in Complementary and Alternative Medicine Use among Patients with Diabetes - Villa-Caballero, Leonel (2010)
OBJECTIVE: To evaluate the effect of ethnicity as a predictor of the use of complementary and alternative medicine (CAM) among patients with diabetes. DESIGN AND SETTINGS: A 16-item questionnaire investigating CAM use was distributed among patients attending the Taking Control of Your Diabetes (TCOYD) educational conferences during 2004-2006. Six TCOYD were held across the United States. Information of diabetes status and sociodemographic data was collected. CAM use was identified as pharmacological (herbs and vitamins) and nonpharmacological CAM. (e.g., prayer, yoga, and acupuncture). RESULTS: The prevalence of pharmacological and non-pharmacological CAM among 806 participants with diabetes patients was 81.9% and 80.3%, respectively. Overall, CAM prevalence was similar for Caucasians (94.2%), African Americans (95.5%), Hispanics (95.6%) and Native Americans (95.2%) and lower in Pacific Islanders/Other (83.9%) and Asians (87.8%). Pharmacologic CAM prevalence was positively associated with education (p = 0.001). The presence of diabetes was a powerful predictor of CAM use. Several significant ethnic differences were observed in specific forms of CAM use. Hispanics reported using frequently prickly pear (nopal) to complement their diabetes treatment while Caucasians more commonly used multivitamins. CONCLUSIONS: Treatment with CAM widely used in persons with diabetes. Ethnic group differences determine a variety of practices, reflecting groups' cultural preferences. Future research is needed to clarify the perceived reasons for CAM use among patients with diabetes in clinical practice and the health belief system associated with diabetes by ethnic group.